Establishment and characterization of arsenic trioxide resistant KB/ATO cells - Yun-Kai Zhang; Chunling Dai; Chun-gang Yuan; Hsiang-Chun Wu; Zhijie Xiao; Zi-Ning Lei; Dong-Hua Yang; X. Chris Le; Liwu Fu; Zhe-Sheng Chen (Elsevier, 2017)
Arsenic trioxide (ATO) is used as a chemotherapeutic agent for the treatment of acute promyelocytic leukemia. However, increasing drug resistance is reducing its efficacy. Therefore, a better understanding of ATO resistance mechanism is required. In this study, we established an ATO-resistant human epidermoid carcinoma cell line, KB/ATO, from its parental KB-3-1 cells. In addition to ATO, KB/ATO cells also exhibited cross-resistance to other anticancer drugs such as cisplatin, antimony potassium tartrate, and 6-mercaptopurine. The arsenic accumulation in KB/ATO cells was significantly lower than that in KB-3-1 cells. Further analysis indicated that neither application of P-glycoprotein inhibitor, breast cancer resistant protein (BCRP) inhibitor, or multidrug resistance protein 1 (MRP1) inhibitor could eliminate ATO resistance. We found that the expression level of ABCB6 was increased in KB/ATO cells. In conclusion, ABCB6 could be an important factor for ATO resistance in KB/ATO cells. The ABCB6 level may serve as a predictive biomarker for the effectiveness of ATO therapy.